Kinetics of silicon extraction into alloy from a mixture of amorphous rocks - V.M. Shevko; N.M. Mirkayev; A.D. Badikova (Journal of Alloys and Metallurgical Systems)
Potential technologically effective raw materials for producing silicon-containing ferroalloys are sedimentary rocks – diatomite, opoka, tripoli, in which silica is predominantly in amorphous form. The article presents the results of studying the kinetics of silicon extraction into alloy from a mixture of amorphous rocks. It was found that in the isothermal mode, the maximum degree of silicon extraction into alloy is 91.4 % at 1800 0C for 60 min. An empirical (experimental-statistical) model of the degree of silicon extraction into alloy was created based on the data of a series of experiments using the second order rotatable experimental design (Box-Hunter design). The model represents a regression dependence on two variables – time (in the range of 20–80 min) and temperature (in the range of 1700–1800 °C). This dependence is obtained as a second degree polynomial. The polynomial’s coefficients are the control parameters of the model. The absolute discrepancy between the experimental and calculated results is from 0.27 % to 2.04 %. The model was validated using the Fisher criterion, which showed that the model adequately reflects the experimental data at a confidence level of 95 %. It was established that when the melting the amorphous rocks, with an increase in the degree of silicon extraction into the alloy, the apparent activation energy decreases, that is a manifestation of diffusion processes, obviously associated with the formation of a silicon carbide layer on the coke surface. The rate of silicon extraction into the alloy when the melting the amorphous rocks is higher than when the melting quartzite. From the amorphous rocks’ mixture, 80 % of silicon is extracted into the alloy at 1800 0C in 50 min, and from quartzite – only in 60 min. The 50 % extraction of silicon into the alloy from the amorphous rocks is characterized by the apparent activation energy Eapp equal to 366.5 kJ, and for quartzite, this energy is higher and is 386 kJ. The similar pattern is observed for the period of inception of the process of silicon extraction into the alloy: Eapp for the amorphous rocks is 422 kJ, and 461 kJ for quartzite. A noticeable improvement in the kinetic parameters of producing a ferroalloy from a mixture of amorphous rocks, in comparison with using quartzite, increases the competitiveness of the technology in the ferroalloy market. This is also facilitated by the significant reserves of amorphous silicon-containing rocks, accessible mining conditions and low prices.